Exploring Cross-Cultural Sensory Acceptance of Vinegar-Based Dipping Sauces: A Taiwanese Consumer Study with Dumplings - Jung-Kuei Ker; Ming-Chen Chiang; Ching-Sung Lee; Yen-Cheng Chen (Foods, 2025)
Vinegar functions not only as a sensory enhancer but also as a culturally embedded culinary element across global food systems. In Taiwanese cuisine, black vinegar represents a traditional staple, particularly associated with dumpling consumption, whereas Italian balsamic vinegar is renowned for its aromatic complexity and nuanced sweetness, highly esteemed in Western gastronomy. Despite their culinary significance, limited empirical research has examined how these culturally distinct condiments are perceived when applied beyond their traditional contexts, especially in iconic national dishes. This study investigates Taiwanese consumers’ cross-cultural sensory responses to dumplings paired with either local black vinegar or imported balsamic vinegar. Through a structured sensory evaluation encompassing appearance, aroma, taste, and overall impression, this research explores how sensory cues and cultural expectations interact to shape flavor preferences. The results indicate that although visual attributes were rated similarly, balsamic vinegar’s distinctive aroma and taste elicited significantly greater sensory engagement, suggesting a latent openness to reinterpretation and hybridization within established food practices. These findings were supported by one-way ANOVA results, which revealed significant differences among the three groups for aroma (F = 6.30, p < 0.01), taste (F = 7.21, p < 0.01), and overall evaluation (F = 15.15, p < 0.001). By integrating sensory analysis with cultural food studies, this research advances the understanding of how multisensory cues influence consumer acceptance across cultural contexts. It further highlights the dynamic interplay between cultural familiarity and sensory novelty in flavor perception. These insights yield practical implications for culinary innovation, global flavor localization, and the development of culturally responsive food products.